Diagnostic Disparity of Previous and Revised American Thoracic Society Guidelines for Idiopathic Pulmonary Fibrosis. Issue 2 (2015) - Fidler, Lee; Shapera, Shane; Mittoo, Shikha; Marras, Theodore K
Abstract : BACKGROUND: A revised guideline for the diagnosis of idiopathic pulmonary fibrosis (IPF) was formulated by the American Thoracic Society (ATS) in 2011 to improve disease diagnosis and provide a simplified algorithm for clinicians. The impact of these revisions on patient classification, however, remain unclear. OBJECTIVE: To examine the concordance between diagnostic guidelines to understand how revisions impact patient classification. METHODS: A cohort of 54 patients with either suspected IPF or a working diagnosis of IPF was evaluated in a retrospective chart review, in which patient data were examined according to previous and revised ATS guidelines. Patient characteristics influencing the fulfillment of diagnostic criteria were compared using one-way ANOVA and χ 2 tests. RESULTS: Revised and previous guideline criteria for IPF were met in 78% and 83% of patients, respectively. Revised guidelines modified a classification based on previous guidelines in 28% of cases. Fifteen percent of patients meeting previous ATS guidelines failed to meet revised criteria due to a lack of honeycombing on high-resolution computed tomography and the absence of a surgical lung biopsy. Patients failing to meet previous and revised diagnostic criteria for IPF were younger. CONCLUSION: The revised guidelines for the diagnosis of IPF classify a substantial proportion of patients differently than the previous guidelines.